Tradisi Ngaruwat Bumi Dalam Kehidupan Masyarakat (Studi Deskriptif Kampung Cihideung Girang Desa Sukakerti Kecamatan Cisalak Kabupaten Subang) - Robi Darwis (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2017)
Ngaruwat Bumi tradition in the village of Cihideung Girang began during the spreading of Islam in West Java, especially in Subang, and the existence of the tradition is merely a proof of respect for society against ancestors. The Cihideung community's view of the Ngaruwat Earth tradition is a form of expression of socio-religious reflection by communicating with the village's ancestors. While the purpose of Ngaruwat Earth tradition 60% of people believe in the ancestors who have been keeping the village of Cihideung Girang from distress. . The implementation of the Ngaruwat tradition is determined by those who have authority in the area and the implementation is done collectively, and carried out in the month of Maulid Nabi or Isra Mi'raj. The meaning of Ngaruwat Bumi trader for Cihideung Girang community is aimed for the happiness and happiness of the afterlife with the citizens of Cihideung Girang, because Ngaruwat tradition must be done with the aim to "dive" or "menyedekahi" the rice fields owned for abundant agriculture. Then the earth that they occupy and planted should be observed so that no interference.